2021
DOI: 10.5703/1288284317285
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of eVTOL Configuration Design for an Air Ambulances System in Japan

Abstract: Electric-vertical-takeoff-and-landing (eVTOL) aircraft, known as urban air mobility or flying cars, are being considered for widespread use as air taxis, emergency medical transportation, sightseeing vehicles, and rural transportation, owing to their reduced-size, low-cost, and low-noise characteristics. In this study, we conduct an interview at a Japanese hospital that currently uses a helicopter for medical emergencies to output the mission profile. Due to current battery-technology limitations, the new air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…For example, "what if the eVTOL was primarily used as a backup for ground ambulances if these cannot arrive in time". The choice of restricting the role of an eVTOL to a rapid responder was motivated by the state of art in eVTOL technology, suggesting patient transport not to be feasible before 2030 (Mihara et al, 2021).…”
Section: Extending the Ems System Using Evtolsmentioning
confidence: 99%
“…For example, "what if the eVTOL was primarily used as a backup for ground ambulances if these cannot arrive in time". The choice of restricting the role of an eVTOL to a rapid responder was motivated by the state of art in eVTOL technology, suggesting patient transport not to be feasible before 2030 (Mihara et al, 2021).…”
Section: Extending the Ems System Using Evtolsmentioning
confidence: 99%
“…A study by Chappelle et al [21] found that near-term electric aircraft are not expected to meet the technical requirements of air ambulance service, nor will they likely provide cost savings over existing services using helicopters. Internationally, Mihara et al [22] conducted a cost analysis of electric vertical take-off and land (eVTOL) aircraft for an air ambulance system in Japan. The study's scenario analysis concludes that differences in battery capacity can have notable differences in future cost models due to the relatively high cost of battery replacements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study's scenario analysis concludes that differences in battery capacity can have notable differences in future cost models due to the relatively high cost of battery replacements. Mihara et al [22] also compare the potential viability of eVTOLs to existing helicopters using a standardized operational concept for air ambulance service. This study builds upon prior literature by studying the feasibility of eVTOLs for aeromedical use in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the tilt mechanism, the thrust vectors generated by redundant propulsors are generally used for attitude control in both multi‐copter (MC) and fixed‐wing (FW) modes in a cruise flight [8], especially for those with ducted fans. Many studies designed the controllers for these types of aircraft by separating the dynamics into two parts: (і) treating the aircraft as a rigid body that moved freely in 3D space driven by virtual control inputs, and (іі) force and torque generated by the actuators.…”
Section: Introductionmentioning
confidence: 99%